Prevalence and Mortality of Pediatrics with Guillain-Barré Syndrome during the COVID-19 Pandemic and Pre-COVID-19 Periods - Ahmadabadi , Farzad; Taghdiri, Mohammadmahdi; Nasehi, MohammadMahdi; Khanipour, Elaheh; Akbari, Samia (Iranian Journal of Child Neurology, 2024)
Objectives Based on case reports, researchers have observed the incidence and clinical manifestations of Guillain-Barré Syndrome (GBS) following COVID-19 infection. Current hypotheses suggest that the risk of GBS may increase with COVID-19, and worsening GBS could elevate the risk of infection and exposure to the virus. This study aimed to assess the cognitive epidemic and mortality of children under 15 years of age with GBS during the COVID-19 pandemic and to compare them to two years earlier without addressing the etiology. Materials & Methods This cross-sectional study was conducted on all children admitted to Iranian hospitals with a diagnosis of GBS and whose clinical information was available in the national flaccid paralysis patient information registration system between April 2018 and April 2021. Results The total number of registered cases of GBS in the pre-COVID-19 period and during this period was 778 cases and 504 cases, respectively (total N=1282), indicating a decrease in registered GBS during COVID-19. The mean age of the patients in the pre-COVID-19 period was 9.00 ± 2.78 years, and during the COVID-19, it was 8.99 ± 2.03 years (P-value =0.998). No significant difference was found in gender distribution between the two periods (P-value =0.427). The total number of paralysis cases studied after 60 days was 14.3% before the COVID-19 period and 17.3% during the pandemic (P-value =0.216). The mortality rate in patients with GBS was 0.13% in the pre-COVID-19 period and 0.19% in the COVID-19 period (P-value =0.757). Conclusion Despite the decline in the frequency of diagnosis and referrals of patients with GBS during the COVID-19 period, no difference was found in the demographic characteristics and clinical outcomes of children with GBS in the pre-COVID-19 period and during this pandemic.